1996
DOI: 10.1021/ja953035l
|View full text |Cite
|
Sign up to set email alerts
|

Thion (RCSOH), Selenon (RCSeOH), and Telluron (RCTeOH) Acids as Predominant Species

Abstract: Thiocarboxylic acids, such as selenocarboxylic acids, exist predominantly in the thioxo form (RCSOH, thion acid) in polar solvents such as tetrahydrofuran (THF) at temperatures below −50 °C. Tellurocarboxylic acids (5) were observed for the first time by acidolysis of the corresponding cesium tellurocarboxylates with hydrogen chloride. The telluroic acids (6) exist predominantly in the telluroxo form (RCTeOH, telluron acid) in THF at temperatures below −70 °C. Telluron acids were reddish to blue violet for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
51
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 14 publications
8
51
1
Order By: Relevance
“…In 1994, Kato and co-workers successfully isolated the selenoic acids RC(@O)SeH from RC(@O)SeNa (R = aryl or alkyl), which is the predominant form in the solid state and in nonpolar solvents, while in polar solvents, the tautomeric form RC(@Se)OH presents predominantly [4]. In 1996, the tellurocarboxylic acids RC(@O)TeH were characterized by the same group [5]. They concluded that for the monochalcogenocarboxylic acids, the chalcogenoxo form RC(@E)OH (E = S, Se, and Te; R = aryl or alkyl) is the predominant species in apolar solvents at low temperature, whereas the chalcogenol acid RC(@O)EH is the predominant species in both the solid state and nonpolar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In 1994, Kato and co-workers successfully isolated the selenoic acids RC(@O)SeH from RC(@O)SeNa (R = aryl or alkyl), which is the predominant form in the solid state and in nonpolar solvents, while in polar solvents, the tautomeric form RC(@Se)OH presents predominantly [4]. In 1996, the tellurocarboxylic acids RC(@O)TeH were characterized by the same group [5]. They concluded that for the monochalcogenocarboxylic acids, the chalcogenoxo form RC(@E)OH (E = S, Se, and Te; R = aryl or alkyl) is the predominant species in apolar solvents at low temperature, whereas the chalcogenol acid RC(@O)EH is the predominant species in both the solid state and nonpolar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…For the spectra with apodized resolutions of 0. 5 Se NMR spectra, respectively. The samples were held at 243 K, and CD 3 OD was used as an external lock and reference.…”
mentioning
confidence: 99%
“…Theoretical results also suggested the thiol form to be the most stable in the gas phase with its presence in both cis and trans conformers. Kato et al [47] on the other hand deduced that the thione form [RC(=S)OH] to be predominant in polar solvents at very low temperatures on the basis of IR and NMR studies. They rationalized the higher stability of thione form in terms of stronger interactions of O-H bond with the polar solvent molecules.…”
Section: Resultsmentioning
confidence: 99%